Bioavailability and metabolism of phenolic compounds from wholegrain wheat and aleurone‐rich wheat bread. Issue 11 (12th July 2016) - Bresciani, Letizia; Scazzina, Francesca; Leonardi, Roberto; Dall'Aglio, Elisabetta; Newell, Michael; Dall'Asta, Margherita; Melegari, Camilla; Ray, Sumantra; Brighenti, Furio; Del Rio, Daniele
Abstract : It is shown that low amounts of bread enriched in aleurone, the metabolically active innermost part of bran, result in equivalent plasma levels of ferulic acid as compared to wholegrain bread. This could suggest that, if the absorbed phenolic metabolites after wholegrain product intake exert health benefits, equal levels can be reached through the consumption of lower doses of refined products enriched in aleurone fraction. Abstract : Scope: This work aimed at investigating absorption, metabolism, and bioavailability of phenolic compounds after consumption of wholegrain bread or bread enriched with an aleurone fraction. Methods and results: Two commercially available breads were consumed by 15 participants on three occasions and matched for either the amount of ferulic acid in the bread or the amount of bread consumed. Urine was collected for 48 h from all the volunteers for phenolic metabolite quantification. Blood samples were collected for 24 h following bread consumption in five participants. A total of 12 and 4 phenolic metabolites were quantified in urine and plasma samples, respectively. Metabolites were sulfate and glucuronic acid conjugates of phenolic acids, and high concentrations of ferulic acid‐4'‐ O ‐sulfate, dihydroferulic acid‐4'‐ O ‐sulfate, and dihydroferulic acid‐ O ‐glucuronide were observed. The bioavailability of ferulic acid was significantly higher from the aleurone‐enriched bread when all ferulic acid metabolites were accounted for. Conclusions: The study shows that low amounts of aleurone‐enriched bread resulted in equivalent plasma levels of ferulic acid as wholegrain bread. This could suggest that, if the absorbed phenolic metabolites after wholegrain product intake exert health benefits, equal levels could be reached through the consumption of lower doses of refined products enriched in aleurone fraction.